Technology adoption in accounting: The role of staff perceptions and organisational context - Jackson, Denise; Allen, Christina (Emerald, 2023)
Technology is widely recognised to be revolutionising the accounting profession, allowing accountants to focus on professional skills and technical knowledge that deliver value for organisational success. Despite the known benefits, it is reported that accountants are not fully leveraging the potential value of certain technologies. To understand why, this study draws on the Technology Adoption Model (TAM) and investigates accounting professionals’ perceptions towards technology, and how these may influence adoption at work. The study gathered online survey data from 585 accounting managers from organisations of varying size and in different sectors in Australia and parts of Southeast Asia. Qualitative data were thematically analysed, and quantitative data were analysed using both descriptive and multivariate techniques. The study highlighted the pivotal role of staff perceptions on the importance and ease of using technology on uptake and successful usage. Findings emphasised important opportunities for organisations to educate accounting staff on the value of technology and optimise their confidence and skills through training and support initiatives, particularly smaller businesses. Marked differences in the orientation towards technology among Australia and Southeast Asian participants illuminate how national work culture and practice can influence technology adoption. The study makes a practical contribution by advancing our understanding of the relative importance and value of certain technologies in different regions and organisation types in the accounting profession. It extends our theoretical understanding of the role of TAM’s core elements to the accounting context, exploring staff’s notions of perceived usefulness and perceived ease of use from the manager’s perspective.